1998
DOI: 10.1002/(sici)1099-1085(19980615)12:7<1021::aid-hyp635>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in properties of an uncropped, ploughed Miamian soil in relation to seasonal erodibility

Abstract: Abstract:Knowledge of seasonal variation in soil structural and related properties is important for the determination of critical periods during which soil is susceptible to accelerated erosion and other degradative processes. The purpose of this research was to evaluate the magnitude of seasonal variations in selected soil and deposited sediment properties in relation to soil erodibility for a Miamian silt-loam soil (Typic Hapludalf) in central Ohio. Erosion plots (USLE-type) were established on a 4 . 5% slop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Their results showed that erodibility was lower from summer to autumn, and that soil was most susceptible to erosion during spring. Bajracharya et al (1998) proposed that seasonal soil erodibility could be predicted using seasonal variation in bulk density, soil organic carbon, and percentage of water-stable aggregates, and suggested that freeze-thaw cycles and partly frozen, saturated conditions during the spring and early summer significantly increased soil erodibility.…”
Section: Seasonal Effects On the Contribution Of The Forest Floor To mentioning
confidence: 99%
“…Their results showed that erodibility was lower from summer to autumn, and that soil was most susceptible to erosion during spring. Bajracharya et al (1998) proposed that seasonal soil erodibility could be predicted using seasonal variation in bulk density, soil organic carbon, and percentage of water-stable aggregates, and suggested that freeze-thaw cycles and partly frozen, saturated conditions during the spring and early summer significantly increased soil erodibility.…”
Section: Seasonal Effects On the Contribution Of The Forest Floor To mentioning
confidence: 99%
“…The stability of soil aggregates is a key property since it affects the movement and storage of water, soi aeration, biological activity, seedling emergence, and root penetration (Gallardo-Carrera et al, 2007). It also affects soil sensitivity to erosion and crusting (Le Bissonnais, 1996;Bajracharya et al,1998;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that aggregate stability is a time dependent variable (e.g. Bullock et al 1988;Caron et al, 1992;Bajracharya et al, 1998;Denef et al, 2001). For now, numerous field monitoring studies have identified a seasonal pattern, with the largest aggregate stabilities recorded in summer and the lowest values in winter (Bullock et al 1988;Blackman, 1992;Chan et al 1994;Dimoyiannis, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, systematic research in this regard is mostly at the macro level and focuses on natural conditions of wind erosion, sandstorm activities and regular sandstorm movement (McHenry and Ritchie, 1977;Sutherland et al, 1991;Bajracharya et al, 1998;Merrill et al, 1999;Zhang et al, 2003;Buschiazzo and Zobeck, 2008). Many previous studies were based on site surveys, fixed position observations and experiments, which were conducted to simulate the process of soil wind erosion (Bilbro and Fryrear, 1994;Fryrear et al, 1994;Thorne et al, 2003;Verheijen et al, 2009).…”
mentioning
confidence: 99%